The impact of six weeks of swimming exercise on the levels of proteins associated with the myelination of hippocampal tissue in Wistar rats with multiple sclerosis - Mohammad Rami; Samaneh Rahdar; Sayed Shafa Marashi; Abdolhamid Habibi (Shahid Beheshti University, 2024)
Background and Purpose: Multiple sclerosis (MS) is a chronic inflammatory, autoimmune, and multi-factorial disease that substantially reduces patients' quality of life. Since physical activity may offer anti-inflammatory and axonal protection benefits to these patients, this study aimed to explore the impact of swimming training on the proteins critical for the myelination of hippocampal tissue in cuprizone-induced rat's model of MS.Materials and Methods: In the current investigation, 20 male Wistar rats with an average age of 12 weeks and the weight of 230 g were purchased and divided randomly into four groups: healthy control, MS control, healthy training, and MS training. The MS disease model was induced by administering food containing 0.5% cuprizone for 12 weeks. Upon confirming MS induction through the rotarod test, rats underwent a six-week swimming protocol. In the first week, they performed 10 min swimming without applying loads, and thereafter the duration of swimming was added by 5 min every week. In order to maintain the adaptations the duration of the swimming for the fifth and sixth weeks was constant and was kept at 30 min. At the end of the training protocol, memory and balance were assessed via shuttle box and rotarod tests. Subsequently, the hippocampal tissue was extracted, and analyzed for determining the proteolipid protein (PLP) and Myelin basic protein (MBP) protein levels by using western blot and the amount of Nerve growth factor (NGF) protein was measured by using the ELISA method. The data were analyzed using one-way ANOVA and post-hoc comparisons were made by using Tukey's test at a significance level of p<0.05.Results: The findings of the shuttle box and rotarod tests revealed that the MS group had impaired memory function and balance maintenance, but these improved significantly after swimming training (p<0.001). No significant difference was observed in the results of the shuttle box and rotarod tests between healthy training and healthy control groups (p>0.05). The results of the present study showed that NGF, PLP and MBP proteins in the patient control group were significantly lower compared to the healthy control group (p<0.05). Furthermore, data analyses showed that the amounts of these proteins increased significantly in the MS training group compared to the MS control group (p<0.05). The results showed that there was a significant difference for NGF and PLP proteins between healthy training group and healthy control group (p<0.05), whereas, no significant differences in MBP protein levels were found between the healthy training and healthy control groups (p>0.05).Conclusion: Based on the current research findings, it can be concluded that swimming exercise has notable anti-inflammatory and neuroprotective effects through favourable molecular adaptations, and it can probably be considered as a safe, non-pharmacological and complication-free method to improve the symptoms in MS patients.